2016
DOI: 10.1007/s10943-016-0320-x
|View full text |Cite
|
Sign up to set email alerts
|

Religious Practices and Self-Care in Iranian Patients with Type 2 Diabetes

Abstract: This study aimed to examine the relationship between religious practices and self-care of patients with type 2 diabetes. A descriptive cross-sectional survey was conducted on 154 diabetic patients who were referred to two general teaching hospitals in Qom City (Iran). Data were collected using demographic questionnaire, private and public religious practices, and summary of diabetes self-care activities questionnaires. Data were analyzed using descriptive statistics and statistical tests including independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 47 publications
3
26
0
1
Order By: Relevance
“…However, such beliefs could sometimes raise hope and strengthen self-care. For example, the results of the study by Heidari et al [47] showed a significantly positive correlation between scores of religious practices and those of self-care activities such as dietary adherence. Therefore, it could be claimed that spirituality and religion could be assumed as important factors affecting disease management in a way that extremes of excess and deficiency in terms of attention to these components in educational interventions to change self-care behaviors could lead to undesirable results.…”
Section: Discussionmentioning
confidence: 99%
“…However, such beliefs could sometimes raise hope and strengthen self-care. For example, the results of the study by Heidari et al [47] showed a significantly positive correlation between scores of religious practices and those of self-care activities such as dietary adherence. Therefore, it could be claimed that spirituality and religion could be assumed as important factors affecting disease management in a way that extremes of excess and deficiency in terms of attention to these components in educational interventions to change self-care behaviors could lead to undesirable results.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies outline various strategies to cope with DD for T2DM outpatients, such as spirituality [19], selfmanagement [18] and family and social support [20][21][22][23][24]. Spirituality is a coping mechanism that is used in several countries, such as Iran [25], Georgia [26] and Malaysia [27].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, they may support and empower patients in making correct decisions (Heidari, Rezaei, Sajadi, Ajorpaz, & Koenig, 2017;Rivera-Hernandez, 2016).…”
Section: Complementary and Alternative Medicine (Cam) Approaches In Tmentioning
confidence: 99%
“…Darvyri et al Williams, 2015). Two of the studies included were cohort studies (Grey et al, 2004), while 11 studies were cross-sectional (Arcury et al, 2007;Newlin et al, 2008;Newlin et al, 2010;How et al, 2011;Lynch et al, 2012;Jafari et al, 2014;Amadi et al, 2015;Rivera-Hernandez, 2016;Berardi et al, 2016;Heidari, Rezaei, Sajadi, Ajorpaz, & Koenig, 2017).…”
Section: Characteristics Of the Studies Included In The Current Systementioning
confidence: 99%